The vaginal microbiota - Kencana, Indah; Yenny, Satya Wydya (Journal of General - Procedural Dermatology and Venereology Indonesia, 2022)
The vagina is an ecosystem consisting of various species of microorganisms (microbiota) that play important role in maintaining vaginal health. The vaginal ecosystem includes a variety of species classified into aerobic and anaerobic microorganisms which are vaginal microbiota (VMB). In the vagina of a healthy woman, 70% of normal microbiota is dominated by the Lactobacillus species. Lactobacillus is a Gram-positive, anaerobic bacterium, and belongs to the group of lactic acid bacteria (LAB). LAB produces lactic acid which plays a role in maintaining vaginal acidity at pH